Karakteristik Fisika-Kimia Kulit Singkong Asal Samarinda dan Akseptabilitas Sensoris Keripiknya Sebagai Camilan Diet - Krishna Purnawan Candra; Ainudin Ainudin; Muhammad Arifin; Yuliani Yuliani (agriTECH, 2020)
The aim of this research was to determine the physicochemical characteristics of cassava peel and the sensory acceptability of its chip form three varieties generally planted in Samarinda, e.g. Pacar, Kuning/Mentega, and Buton cassava. The flour of the three cassavas pulp has HCN content of 14.04, 12.02, and 19.38 mg/kg. A single factor experiment arranged in Completely Randomized Design and each treatment was repeated nine times. Thickness, moisture content, crude fibre content, and ash content of the casava peel were observed, as well as hedonic and quality hedonic sensory acceptability of cassava peel chips for crispiness, taste, aroma, and colour. The result showed that except moisture content, the peel of the three cassava varieties was significantly different (p<0.05) for the thickness, crude fibre content and ash content. The moisture content of the three cassava varieties was around 66.70-70.07%. Peel of Pacar, Kuning/Mentega and Buton cassava has a thickness of 1.52, 2.32, and 1.84 mm, the crude fibre content of 2.70, 2.18, 1.68%, and ash content of 1.19, 2.18, and 0.94%, respectively. The cassava peel chips of the three cassava varieties were significantly different (p<0.05) for hedonic and quality hedonic acceptability (crispiness, taste, aroma, and colour). Pacar cassava showed the most acceptable for crispiness and taste, which has a hedonic and hedonic quality scale of 4.50 (1-7, crispy moderately to crispy) and 5.35 (1-7, taste moderately like cassava to taste like cassava).